Measuring the production efficiency of Al-Furat Company from 1997-2005 - عبد الفتاح جاسم زعلان (Iraqi Journal for Administrative Sciences, 2024)
The industrial sector found that the sector" must acquire importance from Industrial organization because sector have more leading national economic rehabilitation, especially in the third world, according to the measuring and evaluating ability of Industrial productivity sector. It’s considered effective and expresses industrial development in society. because of the growth relation between the amount of resources used in the productivity process and the result of that process. Because its. Considered as economic imputes of productivity process to gain on high ability output with less expense by seeking upon organization courier to distinction. The study aims to achieve productivity ability